Soft-tissue cysticercosis of the forearm: A case report - Banerjee, Divya Jyoti; Patel, Divya Kishorbhai; Chauhan, Himesh Rameshchandra (Indian Journal of Case Reports, 2024)
Isolated muscular cysticercosis is an emerging problem worldwide with varied presentations. Although it commonly affects the brain in the form of neurocysticercosis, it may also present as a pseudotumor-like mass intramuscularly. Although classically associated with measly pork ingestion, it might present in vegetarians too based on several factors. It has a similar presentation to various other diseases often benign, such as lipoma or dermoid, and is thus difficult to diagnose clinically. While ultrasound might give a clue to diagnosis, magnetic resonance imaging (MRI) forms a non-invasive and accurate investigation. Here, we present a case of isolated intramuscular cysticercosis in a 6-year-old female with swelling in the right forearm for the past 1 year. After confirmation of the diagnosis through ultrasound and MRI, medical management was started and surgical excision was planned in view of the abscess. The mass along with the abscess was excised and sent for biopsy. Surgery has to be considered in cases with abscesses although otherwise it might be managed medically.